Autostoppsystem ombord på fartyg - En undersökning om hur autostopp kan undvikas - Larsson, Martin; Oscarsson, Axel (My University, 2014)
The main question of this thesis is to answer how incidents that occur due to auto stop can be avoided. Auto stop in this thesis is when a ship’s main engine automatically shuts down due to critical parameters such as low lubricating oil pressure, over speed or high coolant temperature. An auto stop provides the greatest impact on vessels that only have one main engine because the ship then loses propulsion capability completely, which will result in poor maneuverability. To try to answer the main question, questionnaires were sent to ships with a Swedish connection. Data was also collected from the database Foresea where anonymous reports on incidents are collected. From the questionnaires 50 responses were received and 38 relevant reports were collected from Foresea. Both the surveys and reports show that approximately one third of all auto stops are due to a technical error of the safety system. When studying auto stops due to over speeding of the main engine every second auto stop is due to a technical error, hence many auto stops would be avoided if the safety systems were more reliable. This is something that should be taken seriously; out of the 50 ships that questionnaires were collected from four ships have had very serious incidents. Two of them have run aground and two collided. One way to avoid getting an auto stop when some critical parameter has been exceeded or undershot is to override the alarm. There are always great risks with overriding auto stops and therefore it should only be done in an emergency.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport